Stanowisko władz PRL wobec praskiej wiosny 1968 roku = The position of polish communist authorities towards Prague Spring 1968 - Szczepańska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The democratic changes taking place in Czechoslovakia were observed closely by the Polish People's Republic's authorities. From the beginning, W. Gomułka looked askance at the events - and such was Poland's official position. The alliance between Warsaw and Prague was strengthened a year before and nothing hinted at the crisis to come. In early 1968, friendly visits and routine talks took place, which heralded further cementing of the friendship. But the events in March made W. Gomułka show he was loath to what was going on in the Socialist Republic of Czechoslovakia.
Keywords: Czechosłowacja; Praska Wiosna; Gomułka, Władysław (1905-1982); historia - 1945-1989